Pengaruh Leverage, Opini Audit Tahun Sebelumnya, Pertumbuhan Perusahaan, dan Ukuran Perusahaan terhadap Opini Audit Going Concern - Kusuma Indawati Halim; Kusuma Indawati Halim (Politeknik Ganesha Medan, 2021)
Audit reports are used by auditors to inform the accuracy of the information in the financial statements. The auditor as an independent party has the competence to provide an opinion on the client's financial condition. If it is estimated that the company cannot continue its activities, it is likely that it will get a going concern audit opinion. Audit opinion can help investors and other stakeholders in assessing the status of the company's business continuity. The important thing from a going concern audit opinion is to provide additional information for investors in making investment decisions. This study analyzes the factors that determine going concern audit opinion on manufacturing companies listed on the Indonesia Stock Exchange. The factors tested in this study are leverage, initial opinion, company growth and company size. The study used a sample of 125 companies for the 2014-2018 period. The results of data analysis were obtained from logistic regression tests. The empirical results show that prior opinion and leverage increase the likelihood of receiving a going concern opinion. Meanwhile, company growth and company size have no effect on going concern audit opinion. Nagelkerke's R Square test shows the ability of the factors in this study to explain 63.1% of going-concern audit opinion, while 36.9% is explained by other factors outside the research model. The findings from this study are expected to help investors and other stakeholders to prevent losses if they invest in companies that have the potential to go bankrupt.